2018
DOI: 10.1007/s00380-018-1263-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial compliance is a useful predictor of pulmonary vascular disease in congenital heart disease

Abstract: Histopathological assessment of the pulmonary arteries is crucial to determine the surgical indications in patients with congenital heart disease (CHD) and intractable pulmonary vascular disease (PVD). We aimed to clarify whether pulmonary hemodynamic parameters can predict PVD in patients with CHD and pulmonary arterial hypertension (PAH) We performed histopathological evaluations of lung specimens and cardiac catheterizations in 27 patients with CHD-PAH. We divided these patients into the patients with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… 30–32 Increased pulmonary blood flow, as seen in ASD, VSD, and PDA, can lead to tunica media proliferation, leading to increased pulmonary vessel resistance. 32 , 33 Furthermore, acquired conditions that elevate left atrial pressure (e.g. hypertension or valvular heart disease) may increase the left-to-right shunt in simple ASD.…”
Section: Discussionmentioning
confidence: 99%
“… 30–32 Increased pulmonary blood flow, as seen in ASD, VSD, and PDA, can lead to tunica media proliferation, leading to increased pulmonary vessel resistance. 32 , 33 Furthermore, acquired conditions that elevate left atrial pressure (e.g. hypertension or valvular heart disease) may increase the left-to-right shunt in simple ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Langelben et al reported that an increase in pulmonary blood flow is mainly accommodated by recruitment, with progressive distention according to a further increase in animal models (17). In patients with CHD-PH, Cp rather than Rp can predict the development of pulmonary vascular diseases, such as medial thickness or hypoplastic arterioles, suggesting that a low Cp reflects an early stage of reduced effective pulmonary vascular beds following impaired recruitment and distensibility of the pulmonary capillaries (18). Recently, Cp has gained attention in the management of patients with different conditions of pulmonary arterial hypertension (Table 2) (13, 14, 18-29).…”
Section: Pulmonary Vascular Resistance and Capacitancementioning
confidence: 99%
“…It is a metabolic byproduct of hemoglobin breakdown that also acts as an endogenous antioxidant molecule [ 9 ]. Total bilirubin (TBIL) is well established prognostic factor in heart failure [ 10 ] and PAH [ 8 ]. However, most prior PAH studies focused on patients with predominantly idiopathic or connective tissue disease-related cases.…”
Section: Introductionmentioning
confidence: 99%